2003
DOI: 10.1051/0004-6361:20021719
|View full text |Cite
|
Sign up to set email alerts
|

ISOCAM view of the starburst galaxies M 82, NGC 253 and NGC 1808

Abstract: Abstract. We present results of mid-infrared λ = 5.0 − 16.5 µm spectrophotometric imaging of the starburst galaxies M 82, NGC 253, and NGC 1808 from the ISOCAM instrument on board the Infrared Space Observatory. The mid-infrared spectra of the three galaxies are very similar in terms of features present. The λ > ∼ 11 µm continuum attributed to very small dust grains (VSGs) exhibits a large spread in intensity relative to the shortwavelength emission. We find that the 15 µm dust continuum flux density correlate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 84 publications
3
16
1
1
Order By: Relevance
“…Galaxies with a global color excess are all dominated by their central regions. This is a confirmation of predictions from hydrodynamical models (Athanassoula 1992;Friedli & Benz 1993), according to which a barred perturbation, through tidal torques and shocks, induces substantial mass transfer towards circumnuclear regions. We observe the consequences of these gas flows, i.e.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Galaxies with a global color excess are all dominated by their central regions. This is a confirmation of predictions from hydrodynamical models (Athanassoula 1992;Friedli & Benz 1993), according to which a barred perturbation, through tidal torques and shocks, induces substantial mass transfer towards circumnuclear regions. We observe the consequences of these gas flows, i.e.…”
Section: Discussionsupporting
confidence: 84%
“…We find that the energy ratio F 12.75 /F 11.3 of circumnuclear regions decreases from 0.67 in NGC 1365 to 0.60 in NGC 613 and 5236, 0.52 in NGC 1097 and 0.47 in NGC 5194; in the averaged inner disks of NGC 1365, 5236 and 5194, where it is still measurable, it takes the approximate values 0.5, 0.45 and 0.4 . These figures are much lower than those observed in cores of starburst galaxies by Förster-Schreiber et al (2001), where it can reach 1.7, and argue for a generally small contribution of [NeII] to the spectra. Adopting as the intrinsic F 12.7 /F 11.3 UIB energy ratio the minimum value of F 12.75 /F 11.3 that we measure in our spectra, i.e.…”
Section: Nature Of the Mid-infrared Emitting Speciescontrasting
confidence: 62%
See 1 more Smart Citation
“…instrument. A number of early studies of local and z∼1 galaxies suggested that PAH emission correlates with total dust emission (e.g., Roussel et al 2001;Förster Schreiber et al 2003, 2004, though with some variations with metallicity, ionizing intensity, SFR surface density, and stellar population age (e.g., Normand et al 1995;Helou et al 2001;Alonso-Herrero et al 2004;Engelbracht et al 2005;Hogg et al 2005;Madden et al 2006;Draine et al 2007;Smith et al 2007;Galliano et al 2008;Hunt et al 2010;Sales et al 2010;Elbaz et al 2011;Magdis et al 2013;Seok et al 2014). Recently, Shivaei et al (2017) presented the first statistically significant trends showing lower ratios of the 7.7 μm to total IR luminosity, L 7.7 /L IR , with higher ionization intensity, lower gas-phase metallicity, and younger ages for galaxies at z∼2 from the MOSDEF survey .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have successfully decomposed low resolution mid-infrared spectra of galaxies into three components: A "PDR" component dominated by the aromatic emission features, an "H II" very small grain continuum steeply rising towards longer wavelengths and a hotter "AGN" dust continuum (Laurent et al 2000; see also Sturm et al 2000;Tran et al 2001;Förster Schreiber et al 2003). Dust obscuration can be important (Lutz et al 1998a;Tran et al 2001), with the additional complication of ice features (Spoon et al 2002).…”
Section: Star Formation: Aromatic Emission Featuresmentioning
confidence: 99%